Norwegian General Practitioners' Perspectives on Implementation of a Guided Web-Based Cognitive Behavioral Therapy for Depression: A Qualitative Study - Wilhelmsen, Maja; Høifødt, Ragnhild Sørensen; Kolstrup, Nils; Waterloo, Knut; Eisemann, Martin; Chenhall, Richard; Risør, Mette Bech (JMIR Publications, 2014)
BackgroundPrevious research suggests that Internet-based cognitive behavioral therapy (ICBT) has a positive effect on symptoms of depression. ICBT appears to be more effective with therapist support, but it is unclear what this support should comprise. General practitioners (GPs) have positive attitudes toward ICBT. However, ICBT is rarely used in regular care in general practice. More research is warranted to integrate the potential of ICBT as part of regular care. ObjectiveThe aim of this study was to explore aspects perceived by GPs to affect the implementation of guided ICBT in daily practice. Understanding their perspectives may contribute to improving the treatment of depression in the context of general practice. MethodsA training package (3-day course) introducing a Norwegian translation of the ICBT program MoodGYM was developed and presented to GPs in Norway. Following training, GPs were asked to include guided ICBT in their regular care of patients with symptoms of depression by providing brief, face-to-face follow-up consultations between modules. We interviewed 11 GPs who had taken the course. Our interview guide comprised open questions that encouraged GPs to frame their responses using examples from their experiences when implementing ICBT. Thematic analysis was chosen to explore patterns across the data. ResultsAn overall belief that ICBT would benefit both the patients' health and the GPs' own work satisfaction prompted the GPs to take the ICBT course. ICBT motivated them to invest time and effort in improving treatment. The most important motivating aspects in MoodGYM were that a program based on cognitive behavioral therapy could add a structured agenda to their consultations and empower depressed patients. Organizational aspects, such as a lack of time and varied practice, inhibited the use of ICBT. Inadequate knowledge, recalling the program, and changing own habits were also challenging. The GPs were ambivalent about whether ICBT had a negative impact on the doctor-patient interaction in the module follow-ups. Generally, GPs made an effort to recommend MoodGYM, but the expected module follow-ups were often not provided to patients and instead the GPs returned to standard treatment. ConclusionsGPs' feedback in the present study contribute to our understanding of the challenges of changing treatment for depression. Our findings indicated that recommending ICBT could add to the GP's toolkit. Offering training and highlighting the following aspects may increase recommendation of ICBT by GPs: (1) ICBT is theory-based and credible, (2) ICBT increases the GPs' work satisfaction by having a tool to offer, and (3) ICBT facilitates empowerment of patients in their own health. In addition, the present study also indicated that complex aspects must be accommodated before module follow-ups can be incorporated into GPs' treatment of depression.